Dynamic Evolution of the LPS-Detoxifying Enzyme Intestinal Alkaline Phosphatase in Zebrafish and Other Vertebrates - Yang, Ye; Wandler, Anica M.; Postlethwait, John H.; Guillemin, Karen (Frontiers in Immunology, 2012)
Alkaline phosphatases (Alps) are well-studied enzymes that remove phosphates from a variety of substrates. Alps function in diverse biological processes, including modulating host-bacterial interactions by dephosphorylating the Gram-negative bacterial cell wall component lipopolysaccharide (LPS). In animals, Alps are encoded by multiple genes characterized by either ubiquitous expression (named Alpls, for their liver expression), or their tissue-specific expression, for example in the intestine (Alpi). We previously characterized a zebrafish alpi gene (renamed here alpi.1) that is regulated by Myd88-dependent innate immune signaling and that is required to prevent a host’s excessive inflammatory reactions to its resident microbiota. Here we report the characterization of two new alp genes in zebrafish, alpi.2 and alp3. To understand their origins, we investigated the phylogenetic history of Alp genes in animals. We find that vertebrate Alp genes are organized in three clades with one of these clades missing from the mammals. We present evidence that these three clades originated during the two vertebrate genome duplications. We show that in zebrafish alpl is ubiquitously expressed, as it is in mammals, whereas the other three alps are specific to the intestine. Our phylogenetic analysis reveals that in contrast to Alpl, which has been stably maintained as a single gene throughout the vertebrates, the Alpis have been lost and duplicated multiple times independently in vertebrate lineages, likely reflecting the rapid and dynamic evolution of vertebrate gut morphologies, driven by changes in bacterial associations and diet.